Methods and strategies for involving older adults in branding an online community: the miOne case study - Amado, Pedro (2021)
This paper presents the methods and approaches used in the process of branding an online community for older adults, by actively involving them in its development. It starts by presenting a synthesis of the literature available on the naming and branding processes, the older adults’ characteristics, and relevant participatory design methods used. Then, it presents the participatory branding process, mainly supported by a focus group workshop held with 10 older adults aged 50 and over. The participation of the older adults allowed us to embed their values and identity into the generation of a more familiar brand name, positive values and clearer messaging. Although additional testing with different focus groups is required (e.g. other age range, different ICT skills, or literacy), the results imply that the brand resonates with the target audience.